Absolute or relative stability in plate fixation for simple humeral shaft fractures. Issue 11 (November 2019) - van de Wall, BJM; Theus, C; Link, BC; van Veelen, N; van de Leeuwen, RJH; Ganzert, C; Babst, R; Beeres, FJP
Highlights: Absolute stability reduces time to radiological union in patients with simple humeral shaft fractures compared to relative stability. In simple humeral shaft fractures there is no advantage to perform a minimal invasive approach in respect to biomechanics. There is no benefit in using additional lag screws with regard to time to radiological union or full weight bearing. Adding lag screws does not necessarily assure absolute stability. It may however aid in reduction. Abstract: Introduction: Minimal invasive plating (MIPO) techniques for humeral shaft fractures appear to have fewer complications and higher union rates compared to open reduction and internal fixation (ORIF). It is questionable if this also applies to simple humeral shaft fractures, as simple fractures are generally treated with absolute stability which cannot be obtained with MIPO. This raises the question whether biology or biomechanics is more important in fracture healing. This study was developed to investigate the biomechanical part of this equation. The aim of the study was to compare relative stability to absolute stability in simple humeral shaft fractures with regard to fracture healing Methods: This was a retrospective study of all patients treated with plate fixation for AO/OTA type A1-B3 humeral shaft fractures. Patients were categorized into two groups: absolute stability and relative stability. Both groups were compared with regard to time to radiological union and full weight bearing Results: Thirty patients were included in the relative-stability-group with either an AO/OTA type A (n = 18) or type B (n = 12) humeral shaft fracture and a mean age of 55 (SD 21) years. A total of 46 patients were included in the absolute-stability-group: 27 patients had a type A and 19 type B fracture. The mean age in this group was 45 (SD 19) years. Median follow-up was 12 months (IQR 8–13). Minimally invasive approach was used in 15 (50%) patients in the relative stability group. Time to radiological union was significantly shorter in the absolute-stability-group with a median of 14 (IQR 12–22) versus 25 (IQR17-36) weeks and HR 2.60 (CI 1.54–4.41)(p < 0.001). This difference remained significant after correction for type of approach (adjusted HR 3.53 CI 1.72–7.21) (p 0.001). There was no significant difference in time to full weight bearing. The addition of lag screws in the absolute stability group did not influence time to radiological healing or full weight bearing. Conclusion: Absolute stability for simple humeral shaft fractures leads to a significantly shorter time to radiological union compared to relative stability. The addition of lag screws to gain interfragmentary compression does not reduce fracture healing time.